MEASURING THE EFFECTIVENESS OF A SIMPLIFIED COBIT-BASED IT PROCESS MATURITY ASSESSMENT METHOD - Budi Yuwono; Muhammad Nasri; Rein Nusa Triputra (Faculty of Computer Science Universitas Indonesia, 2009)
We propose a simplified method for measuring the maturity levels of an organization’s information technology (IT) processes that is based on IT Governance Institute’s COBIT (Control Objectives for Information and Related Technology) framework. The method is designed for quickly assessing an organization’s IT process maturity in situations where the availability of information for a more thorough assessment method is very limited. To investigate the accuracy of the proposed method, we evaluate the consistency between the result of the IT process maturity assessment of an organization and the conditions reported by the organization as impediment to the achievement of its IT goals. The underlying assumption is that a condition that is perceived by an organization as a problem will drive the organization to develop a process that can effectively deal with the condition. We show that there is good enough consistency to support the use of the proposed maturity assessment method. Kami mengusulkan sebuah metode sederhana untuk mengukur tingkat kematangan (maturity) dari proses teknologi informasi (TI) suatu organisasi yang didasarkan pada IT Governance Institute’s COBIT framework (Control Objectives for Information and Related Technology). Metode ini dirancang untuk melakukan penilaian dengan cepat dari tingkat kematangan proses TI suatu organisasi dalam situasi di mana ketersediaan informasi untuk metode penilaian yang lebih menyeluruh sangat terbatas. Untuk mengetahui ketepatan metode yang diusulkan, kami mengevaluasi konsistensi antara hasil penilaian kematangan proses TI dari suatu organisasi dan kondisi yang dilaporkan oleh organisasi sebagai rintangan bagi tercapainya tujuan IT. Asumsi yang mendasarinya adalah bahwa suatu kondisi yang dirasakan oleh organisasi sebagai masalah akan mendorong organisasi untuk mengembangkan sebuah proses yang dapat secara efektif menangani kondisi tersebut. Kami menunjukkan bahwa ada konsistensi yang cukup baik untuk mendukung penggunaan metode penilaian kematangan yang diusulkan.